Influence of properties of SAPO's on the one-pot conversion of mono-, di- and poly-saccharides into 5-hydroxymethylfurfural - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (RSC Advances, 2013)
Synthesis of 5-hydroxymethylfurfural (5-HMF) from biomass derived mono-and poly-saccharides is gaining importance because of its usefulness in the preparation of important chemicals. In our work, we have synthesized several silicoaluminophosphate (SAPO) catalysts, and have shown that in the absence of any other pH modifying reagents, those are active in converting mono-and poly-saccharides into 5-HMF under biphasic reaction condition at 175 degrees C. Particularly, SAPO-44 catalyst showed the best activity in the conversion of fructose to yield 78% 5-HMF with 88% selectivity. On the contrary, all other catalysts showed lower yields (H-MOR: 63%, SAPO-5: 32%, 2DCT: 60%). Over SAPO-44, good yields for 5-HMF were observed when glucose (67%), maltose (57%), cellobiose (56%) and starch (68%) were used as substrates. Recycle study carried out with SAPO-44 catalyst in the fructose conversion reaction showed marginal decrease in the activity up to 3rd run and then afterwards constant activity was observed up to 5th run (1st: 78%, 2nd: 71%, 3rd: 66%, 4th: 65%, 5th: 65%). Catalyst characterizations revealed that SAPO catalysts have higher hydrophilic nature than H-MOR (Si/Al = 10) and hence it is postulated that this property may help in achieving better results. Further studies on the catalyst characterizations revealed that SAPO-44 undergoes modifications in its structure. However, ICP-OES data suggests that Al and/or P are not leached out in the solution indicating that change in local environment around elements is possible. The influence of acid amount, type of acid site etc. on the catalytic activity is discussed and found out that strong acid sites are required to boost the 5-HMF yields.

Ionic liquids catalyzed lignin liquefaction: mechanistic studies using TPO-MS, FT-IR, RAMAN and 1D, 2D-HSQC/NOSEY NMR - Singh, Sandip K.; Dhepe, Paresh Laxmikant (Green Chemistry, 2016)
Valorization of a profusely available alternate resource, biomass and in particular its 3-D intricate component lignin into low molecular weight aromatic products are used as platform chemicals and fuel additives, and developing a low temperature catalytic process is imperative in preserving atom efficiency. Ionic liquids, due to their unique properties, offer an advantage to develop such methods under milder conditions. Herein, we show use of -SO3H functionalized imidazolium based various recyclable Bronsted acidic ionic liquids (BAILs) in catalytic quantity under ambient pressure at 120 degrees C for depolymerization of lignin (60 000 g mol(-1)) into THF soluble products with high efficiency (78% yield, 95% +/- 5% mass balance). The decoding of this efficiency by 1D and 2D (HSQC/NOSEY) NMR, FT-IR and RAMAN studies exemplify that the -OH group(s) interact with the electron deficient BAIL cation. The mechanistic insights unraveled in this study open a plethora of opportunities to design catalysts for developing efficient processes.

Isolation of lignin by organosolv process from different varieties of rice husk: Understanding their physical and chemical properties - Singh, Sandip K.; Dhepe, Paresh Laxmikant (Bioresource Technology, 2016)